Effects of Practical Instructional Guide and Teaching Naked Technique on Students’ Achievement, Interest and Retention in Electronics Engineering Technology in Polytechnics in Rivers State - ABULOKWE AMAECHI CLEMENT; ANAELE EDWARD OPARA (Universitas Diponegoro, 2020)
This research study is focused on effects of Practical Instructional Guide (PIG) and Teaching Naked Technique (TNT) on students’ achievement, interest and retention in electronics engineering technology in Polytechnics in Rivers State. Two research questions and hypotheses each were formulated to guide the study which was answered using means and standard deviation while the hypotheses were tested at 0.05 level of significance. The study adopted quasi-experimental research design where the researcher randomly assigned intact classes to groups. The population for the study is 232 Electronics Engineering Technology students in the Polytechnics comprising ND II students of 2019/2020 academic session from two State owned Polytechnics in Rivers State namely: Captain Elechi Amadi Polytechnic, Rumuola in Obi-Akpor Local Government Area of Rivers State with 122 students and Ken Saro Wiwa Polytechnic, Bori in Bori Local Government Area with 110 students. There was no sampling because the population can be managed by the researcher. The instruments for data collection were TNT and PIG lesson plans, Achievement Test (PIG & TNT) of 20 objective test questions, developed practical assessment guide of 35 items and an interest inventory of 20 questions. These instruments were content and face validated by three experts from the Department of Industrial Technical Education (Electronic Technology option), University of Nigeria, Nsukka. The reliability of the instrument was tested using cronbach alpha which has an overall value of 0.79, an mean and standard deviation were used to answer research questions and ANOVA was used to test the formulated hypothesis by applying IBM SPSS version 20. The results of this research support the propositions of instructional theories in the application of two practical instructional techniques with the selection of an appropriate delivery medium of instruction promotes learning. Hence, it was suggested that polytechnic lecturers should be encouraged to employ Practical Instructional Guide (PIG) and Teaching Naked Technique (TNT) Instructional techniques in delivering their lessons, since it enhances academic achievement, interest and retention of students.